The multiplicity of organizing visions - Standing, S.; Standing, C.; Love, Peter; Gengatharen, D. (Elsevier, 2017)
© 2017 Elsevier Inc. Research has shown that information systems adoption decisions are often influenced by organizing visions. Organizing visions provide a legitimation for technology related decision-making and involve a range of influences and perceptions from consultants, industry bodies, policy makers and other firms. This paper is concerned with identifying the mechanisms that underlie the structure of an organizing vision. A range of case studies and a morphogenetic approach, underpinned by critical realist philosophy, are used to demonstrate how organizations respond to organizing visions and how different response communities emerge. We identify and explain the characteristics of the shaper, resistor, coerced, follower and ambivalent communities, their relationship with an organizing vision and the importance of pre-existing conditions.